The effect of susceptibility to false memories and phobia of feeling happy on the parental burden of caregivers of mothers of children with disabilities - Khatatbeh, Yahya M; Al Dawsari, Haifa S H; Alfarraj, Hanan. A; Alsaif, Amal. A; Alharbi, Samiha M (International journal of health sciences, 2024)
Background Raising a child with a disability can be a feeling of isolation and exhaustion, and understanding the health challenges faced by parents with children with disabilities is essential to providing adequate health care. Objectives The current study aimed to find out the impact of both susceptibility to false memories and phobia of feeling happy on the parental burden of caregivers of mothers of children with disabilities. Method: Participated in the study 132 As for Mothers of Children with Disabilities. Their age ranged from (20-over 35) years. The effect of susceptibility to false memories prepared by Ibrahim (2020) And the measure of happiness phobia Barakat (2020)The Parental Burden Scale for Caregivers of Mothers of Children with Disabilities.(Oh & Lee, 2009) Results: Susceptibility to false memories of mothers of children with disabilities was associated with an average level (89.5), a level of happiness phobia (83.0), and a medium level of parenting stress (102. 1). The results also showed that false memory susceptibility had no indirect effect on age, mother status, and happiness phobia variables, and that false memory susceptibility had no effect on happiness phobia, considering age, mother status, and education level variables, except for MRFDSTM.